2017
DOI: 10.1016/j.ejvs.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endovascular Abdominal Aortic Aneurysm Repair in Octogenarians: Meta-analysis and Systematic Review

Abstract: Compared with younger patients, EVAR in octogenarians is associated with a significantly higher but still acceptable peri-operative and midterm mortality rate. Because of similar midterm re-intervention rates, these findings suggest that EVAR remains an appropriate therapeutic approach in the elderly group if comprehensive pre-operative evaluation and post-operative surveillance are incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 33 publications
3
49
5
Order By: Relevance
“…Han et al in a recent meta-analysis reported a higher rate of comorbidities and higher ASA class (3) in the octogenarian population. 1 The present study did not find any difference between the groups concerning different ASA classes, but higher ASA class (4) was an independent predictor of early all cause mortality, independent of age. A modified frailty index was recently suggested as a better discriminator of mortality than other risk factors, especially age and comorbidities.…”
Section: Discussioncontrasting
confidence: 65%
“…Han et al in a recent meta-analysis reported a higher rate of comorbidities and higher ASA class (3) in the octogenarian population. 1 The present study did not find any difference between the groups concerning different ASA classes, but higher ASA class (4) was an independent predictor of early all cause mortality, independent of age. A modified frailty index was recently suggested as a better discriminator of mortality than other risk factors, especially age and comorbidities.…”
Section: Discussioncontrasting
confidence: 65%
“…4,11,17,18 A recent metaanalysis pooled the results of 8 surgical series and reported a perioperative mortality rate of 3.73% in 5876 patients. 19 In contrast, younger patients had perioperative mortality rates of 0%-1.68%. [17][18][19] All patients who died perioperatively in the current study presented with ruptures, which inherently increased their mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, younger patients had perioperative mortality rates of 0%-1.68%. [17][18][19] All patients who died perioperatively in the current study presented with ruptures, which inherently increased their mortality risk. Additionally, the average survival time in this series was 58 months, which is substantial given that the average life expectancy in Canada is 82 years and the average age at intervention is 84 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mid-term follow-up outcomes, which of these issues are equivalent for octogenarians AAAs who underwent EVAR compared with younger AAA patients after EVAR? 9 A. Reintervention rates B. All cause mortality C. Aneurysm-related death D. Aneurysm rupture rate E. Aneurysm growth rate…”
mentioning
confidence: 99%